Treinamento fisioterapêutico intensivo do centro de força corporal, medidas respiratórias e vocais em cantores populares: ensaio clínico randomizado - Frigo, Letícia Fernandez (2016)
Objective: Analyze the vocal, aerodynamic and PH s characteristics before and after a PH s intensive physical therapy training in popular singers. Methods: A randomized clinical trial. Sample composed by singers, shared in Control Group (CG) ans Study Group (SG) that realized the PH s intensive physical therapy protocol. A comparison was made before and after the of the Maximum Phonation Times, voiceless /ė/ of sound pressure level, dynamic range, forced vital capacity (FVC), transversus abdominis activation and maximal expiratory pressures, the glottal source s acoustic voice analysis of was used the Multi Dimensional Advanced Program MDVPA by Kay PENTAX®. Was realized as well, a comparison before and after comparasion about the Simple Phonic Coefficients, Composed Phonic Coefficients, calculation of the ratios s/z, between voiceless and sonorous (ė/e) and the division of Phonation Maximum Time obtained/expected. Conclusion: Was evidenced the improvement of respiratory variables involved in phonation, have not been verified effects on the glottal source measures evaluated in the study, with the exception of two amplitude perturbation measures. The PH s intensive physical therapy training provides the decrease of the ratio of MPTO/MPTE values, suggesting a greater air leak phonation and the normalization of relations s/z and ė/e, suggesting a greater coordination pneumophonic, may bring benefits to the performance of these popular singers.